National Public Assistance Service. A model for streghtening the first health care level - Garmendia-Lorena , Fausto (2021)
The National Public Health Sevice was created in Perú in 1912 as National First Care Service with four sections.  In the year 1945, its Central Care Post was opened as a Emergency Medical Surgical Service and First Aid. In 1951, especialized doctors and medical students  were incorporated, as well as ambulances for home care.  Peripheral posts were also open in many districts in Lima city, Callao and other states. The health care was proveded by care teams in 24 hours shifts, including Sundays.  In 1980 the National Public Health Service was uninstalled and it was migrated to a centralized model with the headquarter at the José Casimiro Ulloa Emergency Hospital. The article arguments for the utility of recovering the model of the National Public Assistance System, understood as a functional component of the National Health System, which will strengthen the first level of health care.